2011
DOI: 10.1002/job.685
|View full text |Cite
|
Sign up to set email alerts
|

Aging and training and development willingness: Employee and supervisor mindsets

Abstract: In this study, we examined individual and situational factors that impact the relationship between age and employee training and development willingness. We proposed that the relationship between age and training and development willingness would be moderated by employees' entity self-theory and perceived developmental support. Furthermore, we investigated supervisors' beliefs about the avoidance orientations of older employees and whether these beliefs would moderate the relationship between employee age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…This is in line with previous reports of negative effects of chronological age on the undertaking of formal learning activities (Kanfer and Ackerman, 2004;Warr, 2001) and positive effects of formal learning activities on employability (Groot and Van den Brink, 2000;Sanders and De Grip, 2004;Van der Heijden et al, 2009). One reason for the reduced participation in formal learning activities of older employees is the unwillingness of employers to send older people to trainings (Grima, 2011;Van Vianen et al, 2011), often due to non-inclusive and discriminatory employer attitudes and policies (Billett and Van Woerkom, 2008). Informal learning, however, is less dependent on the employers' resources and we did not find information, feedback, and help seeking to mediate the relationship between chronological age and employability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous reports of negative effects of chronological age on the undertaking of formal learning activities (Kanfer and Ackerman, 2004;Warr, 2001) and positive effects of formal learning activities on employability (Groot and Van den Brink, 2000;Sanders and De Grip, 2004;Van der Heijden et al, 2009). One reason for the reduced participation in formal learning activities of older employees is the unwillingness of employers to send older people to trainings (Grima, 2011;Van Vianen et al, 2011), often due to non-inclusive and discriminatory employer attitudes and policies (Billett and Van Woerkom, 2008). Informal learning, however, is less dependent on the employers' resources and we did not find information, feedback, and help seeking to mediate the relationship between chronological age and employability.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to the relation between age and formal learning, most studies indicate that older people are less interested in attending formal trainings (Kanfer and Ackerman, 2004;Livingstone, 1999;Warr and Birdi, 1998;Warr, 2001) and also are offered fewer opportunities to do so (Grima, 2011;Urwin, 2006;Van Vianen et al, 2011). This negative relationship may be explained by negative stereotypes against older workers (Kunze et al, 2013;Maurer et al, 2003;Wrenn and Maurer, 2004) and by financial considerations, as the potential pay-off period for any investments in employees is shorter the closer the employee is to retirement age.…”
Section: Chronological Age Learning and Employabilitymentioning
confidence: 99%
“…First, the finding that older workers are expected to contribute their knowledge, but might not be considered appropriate knowledge recipients by their colleagues, might have detrimental effects on older workers’ perceived developmental opportunities. As these opportunities have been shown to be important for many older workers who wish to develop their knowledge and skills until retirement (Armstrong‐Stassen & Stassen, ; Van Vianen, Dalhoeven, & de De Pater, ), organizations should be careful not to disregard older workers when creating opportunities for development. Second, organizations can offer awareness trainings in which employees reflect on the age norms that guide their knowledge transfer behaviour at work.…”
Section: Discussionmentioning
confidence: 99%
“…This learning value depends on key features of the work, such as high quality job assignments and the degree of challenge and growth potential, especially with regard to the ability to utilize one's knowledge and skills. Supervisors fulfill a crucial role with regard to the assignment of challenging tasks and activities (Van Vianen et al, 2011). However, Maurer (2007) found that older workers more often receive routine tasks rather than complex and challenging job assignments that stimulate development (p. 168), herewith endangering their future employability (Van der Heijden et al, 2009a).…”
Section: Theoretical Background and Formulation Of Hypothesesmentioning
confidence: 99%